Pemberdayaan Remaja Masjid Dan Perannya Dalam Pendidikan Islam - Beny Sintasari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
Youth empowerment and mentoring aims to make them a good young generation; namely adolescents who are righteous, faithful, knowledgeable, skilled and have noble character. To foster Muslim teenagers, it can be done in various approaches, including through the activities of youth mosques. Mosque youth is an organization that accommodates Muslim youth activities in prospering mosques. Mosque youth is an alternative forum for youth development that is good and needed by the people. By being oriented towards mosque, Islamic, scientific, youthful and skill activities, this organization can provide opportunities for its members to develop themselves according to their talents and creativity. Mosque youth have a very important role because mosque youth is an organization that really thinks about the development of Islam. Mosque youth play a role in the spread of Islamic culture. Through mosque youth, we can gradually instill Islamic values ??in children, so that they can fortify the Muslim generation in every activity.